The use of dental materials in periodontal therapy in Malaysia: An Islamic legal maxim analysis - Wan Abdul Fattah Wan Ismail; Nik Salida Suhaila Nik Saleh; Haslinda Ramli; Nadia Halib; Setiyawan Gunardi; Nur Akilah Abdul Ghaffar; Shofian Ahmad (Universiti Kebangsaan Malaysia, 2024)
Non-Indexed Publication